PERCERAIAN DALAM ISLAM DAN KRISTEN - Hasan Bakti Nasution; Agusman Damanik; Deska Afriani Caniago (Studia Sosia Religia, 2022)
Divorce or often also referred to as talak in Islam is a breaker of husband and wife relations from a legal marriage relationship according to Islamic religious rules and the state, in Islam divorce is considered something that is permissible but is not liked by Allah. Meanwhile, divorce in Christianity is considered as a deviation from God's teachings, which is not allowed at all until death do them part. The purpose of this study is to discuss the views of Islam and Christianity but this divorce is very vulnerable to people doing at this time. The basic question in this research is what is meant by divorce and how do Muslim and Christian religious leaders view this divorce. This research is a field study research that uses a library research methodology. And collect the results of interviews with Islamic and Christian religious figures as evidence of research material. The findings obtained in this study are that divorce in Islam and Christianity is something that is hated by Allah but still many people take the act of divorce.